Best approach to measuring the inferior vena cava in spontaneously ventilating patients. (February 2015) - Baker, Elinor C.; Pott, Jason; Khan, Faisal; Freund, Yonathan; Harris, Tim
<x xml:space="preserve">Abstract</x> The objective of this study was to establish the reliability of different measurements of inferior vena cava (IVC) size and respiratory variation in response to changes in circulating volume. Transabdominal ultrasound measurements of the IVC were obtained in longitudinal (B and M modes) and transverse planes (B-mode height and ellipse circumference) during inspiration and expiration, and inferior vena cava collapsibility indices (IVCci) were calculated. Measurements were repeated following venesection of ∼450 ml. Thirty patients underwent venesection. Their IVCci increased significantly for transverse and longitudinal height measurements following venesection, but not for transverse circumference measurements. Transverse views were inadequate in 27% of patients, compared with 7% for longitudinal views (P=0.04). Changes in IVCci are sensitive to small changes in circulating volume. Measurements are most frequently achieved in the longitudinal plane. There is an urgent need for standardization of sonographic IVC measurement techniques.